Answer :

Given,

In ABC,


B - A = C - B


B + B = A + C


2B = A + C (i)


Now,


A + B + C = 180°


B = 180 - (A + C) (ii)


Using (i) in (ii), we get


B = 180 - 2B


3B = 180°


B = 60°


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that the anRS Aggarwal & V Aggarwal - Mathematics

If the sides of aRD Sharma - Mathematics

D is any point onNCERT Mathematics Exemplar

In a triangle RD Sharma - Mathematics

In Δ ABCRD Sharma - Mathematics

In Δ PQRRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal & V Aggarwal - Mathematics

Prove that the peRD Sharma - Mathematics

In Fig. 10.25, <iRD Sharma - Mathematics

In a <span lang="RD Sharma - Mathematics